Os impactos da COVID-19 para o transporte de alimentos perecíveis. - Barcelo, Marcia Pinto (Universidade Federal do Tocantins, 2023)
The pandemic caused by the new coronavirus has impacted several sectors, including the transport of perishable food, which has complex logistics and requires extra safety and preservation procedures. The study started from the need to analyze the perishable food transport sector in the context of the pandemic, with the aim of exploring its consequences for the sector. To achieve this goal, the methodology used was bibliographic research, which consisted of the study of materials such as books and scientific articles, as well as publications on websites and specialized journals. With the research carried out, it was possible to see that the food transport sector, even suffering losses due to the difficulty in the flow of production, was one of the least affected, even with some sectors being favored by the international scenario. The current crisis has exposed the weaknesses and vulnerabilities of supply chains, but we already have the technology and knowledge necessary to prepare ourselves so that in times like these the effects are mitigated, allowing us to find solutions that favor all sectors of the economy.